Microbiologically influenced corrosion of Al–Cu–Li alloy by Pseudomonas aeruginosa - Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; Azocar-Guzman, M; Jimenez-Arevalo, V; Jimenez-Arevalo, V (Elsevier Editora Ltda, 2025)
This study investigates microbiologically influenced corrosion (MIC) of the Al–Cu–Li alloy AA2060-T8 caused by Pseudomonas aeruginosa . Key parameters—bacterial population (OD600), specific biofilm-forming capacity (SBF), pH, and open circuit potential (OCP)—were monitored over time and correlated with bacterial growth stages. A colonization time range between 3 and 10 h was identified (OD600: 0.23–0.67), during which P. aeruginosa produced a critical biofilm amount (SBF: 0.14–0.74) sufficient to sustain irreversible adhesion on the alloy surface, as indicated by the OCP increase from 4 h. Furthermore, a pH decrease from 7.6 to 6.8 was observed during the exponential stage, likely reaching pH 3.5–4.5 within colony cores. This could have created conditions that facilitated the destabilization of the oxide layer beneath the biofilm, making the alloy more susceptible to localized corrosion. After 24 h of exposure to the MIC testing solution, cross-sectional analysis of the alloy revealed discontinuities within the biofilm, which allowed the electrolyte to reach the alloy surface and promote the formation of local differential cells. Thus, MIC of the AA2060-T8 alloy caused by P. aeruginosa is mainly due to the combined effects of pH decrease and the formation of discontinuities acting as channels within the biofilm. These findings provide new insights into the MIC of Al–Cu–Li alloys, paving the way for future protection strategies against MIC. © © 2025. Published by Elsevier B.V.